Antimony resistance during Visceral Leishmaniasis: A possible consequence of serial mutations in ABC transporters of Leishmania species - Sinha, Sukrat (Biomedical Informatics, 2011)
Visceral Leishmaniasis is a macrophage associated disorder for the treatment of which antimony based drugs like SAG and SSG were the first choice in the recent past. The clinical value of antimony therapy is now declined against VL because increasing cases of Sodium Antimony Gluconate (SAG) resistance have reached outstanding proportion in Bihar, India. Within this context we looked into the protein sequences of ABC transporters of Leishmania spp associated with Visceral Leishmaniasis that are known to play a crucial role in the development of multidrug resistance (MDR). Our studies consisting of ClustalW, Phylogeny and TCOFFEE have pinpointed that ABC transporters have enormously diverged during the process of evolution even within the identical species strains resulting in insignificant homology and subdued conservation amongst the aminoacid residues. Moreover these amino acid residues remain susceptible to mutations in evolutionary era as indicated by high frequency of variations by the variability studies. Hence we predict that during the process of evolution a series of frequent mutations might have led to changes in the ABC transporters favorable to effluxing the drug thereby making the Leishmania species prone to resistance against the efficient first line drug SAG, used for combating VL. This selection has made them to survive efficiently in the adverse circumstances of antimony based antileishmanial therapy regime.